2015
DOI: 10.5194/acp-15-8847-2015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, microstructure, and hygroscopic properties of aerosol particles at the Zotino Tall Tower Observatory (ZOTTO), Siberia, during a summer campaign

Abstract: In this study we describe the hygroscopic properties of accumulation-and coarse-mode aerosol particles sampled at the Zotino Tall Tower Observatory (ZOTTO) in central Siberia (61 degrees N, 89 degrees E) from 16 to 21 June 2013. The hygroscopic growth measurements were supplemented with chemical analyses of the samples, including inorganic ions and organic/elemental carbon. In addition, the microstructure and chemical compositions of aerosol particles were analyzed by x-ray micro-spectroscopy (STXM-NEXAFS) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 106 publications
0
43
1
1
Order By: Relevance
“…Our independent measurements performed from 15 to 25 December 2011 showed that the main inorganic anthropogenic ions are sulfates (∼ 32 %), nitrates (∼ 6 %), ammonium (∼ 5 %), and minor components such as sodium (∼ 1 %) and potassium (∼ 1 %). The contribution of other ions is less than 1 % (Mikhailov et al, 2015b).…”
Section: Polluted Winter Airmentioning
confidence: 95%
See 3 more Smart Citations
“…Our independent measurements performed from 15 to 25 December 2011 showed that the main inorganic anthropogenic ions are sulfates (∼ 32 %), nitrates (∼ 6 %), ammonium (∼ 5 %), and minor components such as sodium (∼ 1 %) and potassium (∼ 1 %). The contribution of other ions is less than 1 % (Mikhailov et al, 2015b).…”
Section: Polluted Winter Airmentioning
confidence: 95%
“…A consequence of the atmospheric evolution of SOA is the convergence of its chemical composition and physical properties (Andreae, 2009). In particular, the CCN and hygroscopic properties of the SOA formed in the rain forest and boreal forest environments become very similar (Mikhailov et al, 2015b;Pöhlker et al, 2016).…”
Section: Sitementioning
confidence: 99%
See 2 more Smart Citations
“…OC coatings on inorganic particles can induce an early deliquescence of particle surface compared to that of the pure inorganic compounds (Li et al, 2014a). Recently, Mikhailov et al (2015) found that the semi-solid state of the OC coating can lead to kinetic limitations of water uptake and release during hydration and dehydration cycles in the background area. OC dominated in fine particles, accounting for 43 % of mass on average, followed by sulfate (28 %) and nitrate (1 %) (Du et al, 2015).…”
Section: Mixing Mechanisms Of Aged Aerosol Particlesmentioning
confidence: 99%